The Effect of Internal Audit of Cash Disbursements on Internal Control of Cash Disbursements: Study At One of The Companies in The Field of Broiler Farming in Bandung - Fauziah, Salma Muna; Mialasmaya, Siti; Ramdani, Adam; Damayanti, Indah; Purana, R. Deni (Center of Research, STIE Pasundan, Bandung, Indonesia., 2023)
The present research investigates the impact of Internal Cash Audit on the Internal Control of Cash Expenditure within a poultry farming enterprise in Bandung. This study aims to examine and assess the impact of Internal Cash Audit on the Internal Control of Cash Expenditure within the broiler chicken farming industry. The research methodology employed in this study is quantitative, involving gathering data through the distribution of questionnaires and subsequent statistical analysis. The study population comprises personnel engaged in the organization's financial operations and internal control procedures. The study's results suggest that Internal Cash Audit remarkably affects the Internal Control of Cash Expenditure. By conducting a comprehensive analysis of cash expenditure transactions and associated documentation, internal auditors can detect any discrepancies or irregularities that could potentially jeopardize the organization. Furthermore, the research emphasizes the significance of deploying efficient internal control mechanisms to guarantee precise and regulated cash outflows. The findings of this study enhance comprehension of the correlation between Internal Cash Audit and the Internal Control of Cash Expenditure within the distinct setting of the poultry farming sector. The study's results may guide the organization's leadership in enhancing its internal control mechanisms and maximizing the efficiency of its Internal Cash Audit procedures.